Analisis Pajak Reklame Serta Kontribusi Terhadap Pendapatan Asli Daerah Di Pemerintah Daerah Kabupaten Rokan Hulu - Nurhayati Nurhayati; Ahok Alpa Beta (Fakultas Ekonomi Universitas Pasir Pengaraian, 2019)
This research aims to quantify and analyze how big a contribution Tax Revenue against the Original Billboard area (PAD) in the local Government District of Rokan Hulu. In the study conducted an analysis of the quantitative data, that is the method that compares a specific number which is then drawn conclusions from these calculations. The results of the survey in 4 subdistricts with 49 taxpayer with potential billboards as much as 94 by the calculation result is Rp. 2.834.625.704,. Where the tax potential of the largest billboard is located in the tip of the rock with the amount of Rp. 2.184.672.788, and the smallest sub-district is Rp. 102.995.441 tambusai, based on calculations that have been done, then there is the existing of selesih among the potential acquisition target is Rp. 1.834.625.704, and if compared with the realization of Rp 1,705,504,289,. The effectiveness of the Tax Reklmae for the year 2017 Rokan Hulu, with the results of its effectiveness of 113% by category. While the tax contribution for advertising revenue against the original area just 1% with the classification is very less.